Compressive strain formation in surface‐damaged crystals. Issue 3 (23rd April 2020) - Ferrari, Claudio; Beretta, Sara; Rotunno, Enzo; Korytár, Dusan; Zaprazny, Zdenko
Abstract : The formation of compressive strain in surface‐damaged crystals after polishing or grinding is explained by formation of dislocations which penetrate into the damaged layer of the crystal and have common Burgers vector components parallel to the surface. Abstract : The mechanism of formation of residual strain in crystals with a damaged surface has been studied by transmission electron microscopy in GaAs wafers ground with sandpaper. The samples showed a dislocation network located near the sample surface penetrating to a depth of a few micrometres, comparable to the size of abrasive particles used for the treatment, and no other types of defects were observed. A simple model for the formation of a compressive strain induced by the dislocation network in the damaged layer is proposed, in satisfactory agreement with the measured strain. The strain is generated by the formation of dislocation half‐loops at the crystal surface, having the same component of the Burgers vectors parallel to the surface of the crystal. This is equivalent to the insertion of extra half‐planes from the crystal surface to the depth of the damaged zone. This model can be generalized for other crystal structures. An approximate calculation of the strain generated from the observed dislocation distribution in the sample agrees with the proposed model and permits the conclusion that this mechanism is in general sufficient to explain the observed compressive strain, without the need to consider other types of defects.